A rare case of minor salivary gland tumor presenting as parapharyngeal tumor - E., Rajesh Goud; B., Manideep; Paladugu, Malyadri; Gupta, Somnath (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Parapharyngeal space tumours (PPS) are benign, uncommon located in the head and neck region. Pleomorphic adenoma the most prevalent type of salivary gland tumour can develop from the salivary glands or start in the deep lobe of the parotid gland and spread into PPS. A 59-year-old male presented with complaints of dysphagia, voice change and swelling in the soft palate. PPS tumour was detected with endoscopy, biopsy confirmed it as salivary gland tumour and PET-CT scan findings revealed a large hyper metabolic solid soft tissue density lesion in left parapharyngeal space with local extent. Tumour excision was done through transcervical approach. Biphasic components were highlighted by CK7, SOX10, SMA, P63 using immunohistochemistry (IHC) confirming benign mixed salivary gland tumor pleomorphic adenoma. Patient was treated with IV antibiotics, IV PPI’s, IV analgesics, IV antiemetics and discharged in stable condition. PET-CT, IHC serves a vital role in diagnosis and confirmation of severity of tumour. The transcervical approach is the preferred technique for excising tumours in the parapharyngeal space that have narrow attachments.